Activation of Peroxisome Proliferator-Activated Receptor-Gamma by Glitazones Reduces the Expression and Release of Monocyte Chemoattractant Protein-1 in Human Mesothelial Cells. (7th February 2012) - Sauter, Matthias; Kastenmüller, Kathrin; Belling, Franziska; Wörnle, Markus; Ladurner, Roland; Mussack, Thomas; Sitter, Thomas
Abstract : Human peritoneal mesothelial cells (MC) play an important role in inflammatory processes of the peritoneal cavity by producing various cytokines and chemokines, such as monocyte chemoattractant protein-1 (MCP-1). The present study was designed to assess the effect of the peroxisome proliferator-activated receptor-gamma- (PPARγ -) activator rosiglitazone on the mesothelial MCP-1 expression and release. Primary cultures of MC were obtained from omental tissue. MCP-1 antigen concentrations were measured in the cell supernatant by ELISA and MCP-1 mRNA levels by real-time polymerase chain reaction. The presence of PPARγ on MC was assayed in a Western Blot analysis. MC constitutively express PPARγ . Activation of this receptor via rosiglitazone (0, 1–10 μmol/L) resulted in significantly reduced amounts of mesothelial MCP-1 release as well as MCP-1 mRNA. The use of the PPARγ inhibitor GW-9662 could completely prevent the rosiglitazone effects. Rosiglitazone was also effective in reducing TNFα -induced enhanced secretion of MCP-1. Our findings indicate that glitazones are effective in reducing constitutive and TNFα -stimulated mesothelial MCP-1 mRNA expression and release.